Investigating the influence of working status changes on physical activity and non-communicable diseases in Korean middle-aged and older adults: insights from a longitudinal panel study - Jeong-Hui Park; Ju-Pil Choe; Jisu Kim; In-Whi Hwang; Jung-Min Lee (BMC Public Health)
Abstract Background Non-communicable diseases (NCDs) are a major global health challenge and occupational status is a critical determinant influencing NCD development, yet many cross-sectional studies have only linked current occupational status with specific diseases, overlooking broader temporal factors. The primary aim of the present study was to comprehensively elucidate the intricate interplay between alterations in working status, NCDs, and physical activity (PA) among Korean middle-aged and older adults, employing a longitudinal panel study design. Methods This study utilized longitudinal data from the Korean Longitudinal Study of Aging, covering the period from 2006 to 2020, with a median follow-up duration of 10 years. (n = 5101 participants aged 45 years and older). Changes in working status were categorized, focusing on (1) yes–yes (e.g., indicative of sustained employment), (2) yes–no (e.g., denoting a transition from employment to non-employment), (3) no–yes (e.g., representing a shift from non-employment to employment), and (4) no–no (reflecting a continual non-employment status). PA was defined as the total minutes of moderate-to-vigorous PA per week and categorized into two groups: <150 min/week and ≥ 150 min/week. Confounding factors included age, gender, marital status, education level, and body mass index. Relative risk ratios (RRR) with 95% confidence intervals (CI) were calculated using random-effect multinomial logistic regression. Results Individuals who were currently employed (adjusted RRR = 0.688, 95% CI = 0.656–0.722, p < 0.001) or who transitioned to employment (adjusted RRR = 0.755, 95% CI = 0.707–0.807, p < 0.001) had a reduced risk of physical inactivity. However, employed individuals had an increased risk of cardiovascular diseases (yes-yes: adjusted RRR = 1.653, 95% CI = 1.547–1.766, p < 0.001; no-yes: adjusted RRR = 1.168, 95% CI = 1.100–1.240, p < 0.001) and diabetes (yes-yes: adjusted RRR = 1.535, 95% CI = 1.464–1.610, p < 0.001; no-yes: adjusted RRR = 1.124, 95% CI = 1.078–1.173, p < 0.001). Additionally, current workers exhibited higher risks of cancer (yes-yes: adjusted RRR = 1.871, 95% CI = 1.721–2.035, p < 0.001; no-yes: adjusted RRR = 1.089, 95% CI = 1.018–1.166, p = 0.014) and chronic respiratory diseases (yes-yes: adjusted RRR = 1.467, 95% CI = 1.307–1.648, p < 0.001; no-yes: adjusted RRR = 1.121, 95% CI = 1.011–1.242, p = 0.029). Conclusion This longitudinal study revealed that individuals engaged in or transitioning to employment displayed a reduced likelihood of regular PA. Moreover, those with work history, transitioning, or consistently working, exhibited increased vulnerability to all NCDs compared to those without work experience.